Diabetes, disability, and dementia risk: Results from the Hispanic Established Populations for the Epidemiologic Studies of the Elderly (H-EPESE) - Vásquez, Elizabeth; Gadgil, Meghana A; Zhang, Weihui; Angel, Jacqueline L (International journal of social psychiatry, 2022)
Background: Emerging research has elucidated pathophysiological relationships among diabetes, disability, cognitive impairment, and incident dementia. However, the relationships between diabetes, disability, and dementia have been largely underexamined in Latino populations, which have a disproportionate prevalence of diabetes and its complications. Aims: This study examines diabetes as a risk factor for subsequent disability and dementia risk in a Mexican-origin older adult sample. Methods: The data are drawn from eight waves (1993–2013) of the Hispanic Established Populations for the Epidemiologic Study of the Elderly (HEPESE; N = 3,050, mean age at baseline = 73.6 (±6.8)). Respondents’ diabetes status at baseline was ascertained by self-report. Disability was assessed using eight functional domains assessed through the Lawton Instrumental Activities of Daily Living (IADL) Scale. Dementia risk was assessed using a Mini-Mental Status Exam (MMSE) score below 18 and the need for aid with at least two IADLs. We used multivariable Cox proportional hazards models to predict the relation between diabetes and time to disability, cognitive impairment, and incident dementia, adjusting for age at migration, socioeconomic status, acculturation, and health status. Results: At baseline, diabetes prevalence was 28.1%, and 37.7% had IADL disability. Diabetes was associated with a higher risk of developing dementia (Hazard Ratio (HR) = 1.22, p < .001) over the approximetely 20 year study period. In addition, immigrants who migrated at age 50 or older had a higher dementia risk (HR = 1.35, p = .01) when compared to their US-born counterpart. Conclusion: Our results highlight the importance of better characterizing the role of diabetes and nativity in the co-occurrence of disability and dementia risk.